Penerapan Pembelajaran Project Based Learning untuk Meningkatkan Kemampuan Berkomunikasi Peserta Didik SMP dalam Pembelajaran di Kelas - Herisa Sintia; Desy Safitri; Sujarwo (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2025)
This study aims to examine the effectiveness of the Project Based Learning (PjBL) model in enhancing the communication skills of junior high school students through a literature review approach. The study critically analyzes a range of scholarly literature and recent research findings concerning the implementation of PjBL, particularly in the context of developing oral, written, and interpersonal communication skills within primary education settings. The findings indicate that PjBL fosters an active, collaborative, and contextual learning environment that significantly contributes to the improvement of students’ communication abilities. Through project completion that involves exploration, presentation, and group interaction, learners are encouraged to articulate ideas effectively, engage in active listening, and produce writing with logical and argumentative structure. Moreover, the model has been shown to enhance students' self-confidence, independence, and sense of responsibility toward their own learning process. Nonetheless, the implementation of PjBL continues to face several challenges, including limited instructional time, insufficient teacher understanding of meaningful project design, and inadequate supporting resources. Without systemic support and continuous professional development for educators, the application of this model risks becoming a mere formality with little substantive impact. Therefore, this study recommends further empirical research using a mixed-methods approach to investigate the effectiveness of PjBL across various subjects and educational levels. Such studies are expected to strengthen the theoretical foundation and promote the adoption of PjBL as a transformative learning strategy in shaping learners.